Engaging with records and archives histories and theories - Foscarini, Fiorella ca. 20./21. Jh; MacNeil, Heather 1957-; Mak, Bonnie; Oliver, Gillian ca. 20./21. Jh (Facet Publishing, 2016)
This collection provides a multifaceted response to today's fascination with the idea of the archive and showcases the myriad ways in which archival ideas and practices are being engaged and developed by emerging and internationally renowned scholars. Engaging with Records and Archives offers a selection of original, insightful and imaginative papers from the Seventh International Conference on the History of Records and Archives (I-CHORA 7). The contributions in this volume comprise a wide variety of views of records, archives and archival functions, spanning diverse regions, communities, disciplinary perspectives and time periods. From the origins of contemporary grassroots archival activism in Poland to the role of women archivists in early 20th century England; from the management of records in the Dutch East Indies in the 19th century to the relationship between Western and Indigenous cultures in North America and other modern archival conundrums, this collection reveals the richness of archival thinking through compelling examples from past and present that will captivate the reader